1994
DOI: 10.1152/ajpheart.1994.267.2.h587
|View full text |Cite
|
Sign up to set email alerts
|

Polyamine effects on [Ca2+]i homeostasis and contractility in isolated rat ventricular cardiomyocytes

Abstract: In electrically stimulated myocytes loaded with the fluorescent Ca2+ indicator indo 1-acetoxymethyl ester, spermine induced a dose-dependent (100-500 microM) negative inotropic effect, which was associated with a decrease in the magnitude of the cytosolic Ca2+ concentration ([Ca2+]i) transient but not with changes in myofilament responsiveness to Ca2+. Spermidine induced a less pronounced negative inotropic effect, whereas putrescine did not modify myocyte contraction. In the unstimulated state, spermine did n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 0 publications
1
11
0
2
Order By: Relevance
“…It is well known that ornithine is the precursor for the synthesis of polyamines such as spermine, spermidine, and putrescine. There have been reports that polyamine concentration alters K ϩ channel current in myocytes (41), can decrease inotropy by superfusion of exogenous polyamines (39), and can decrease calcium sensitivity (20). However, these studies show the effects of direct application of high-concentration exogenous polyamines, which is likely distinct from the smaller changes in endogenous ornithine that result from modulation of arginase activity.…”
Section: Discussionmentioning
confidence: 95%
“…It is well known that ornithine is the precursor for the synthesis of polyamines such as spermine, spermidine, and putrescine. There have been reports that polyamine concentration alters K ϩ channel current in myocytes (41), can decrease inotropy by superfusion of exogenous polyamines (39), and can decrease calcium sensitivity (20). However, these studies show the effects of direct application of high-concentration exogenous polyamines, which is likely distinct from the smaller changes in endogenous ornithine that result from modulation of arginase activity.…”
Section: Discussionmentioning
confidence: 95%
“…Plasma levels of spermine are extremely variable, ranging from the nanomolar to the micromolar range [37], and the most frequently reported value for spermine content in rat heart is around 400 nmol/g [38]. However, local levels of spermine may be much higher than the circulating concentration, a s reported in the nervous system, where presynaptically released spermine achieves high millimolar levels within synaptic clefts [39].…”
Section: Discussionmentioning
confidence: 99%
“…The administration of putrescine to the organ bath elicited a positive inotropism and increased intracellular cAMP levels in isolated left atrium of rats; however, a lack of effect after extracellular administration of putrescine and negative inotropism by spermidine and, specially, spermine has been reported in isolated rat ventricular cardiomyocites 27 and isolated rat heart. 28 The link between intracellular polyamines and cAMP during androgen-elicited positive inotropism was subsequently studied, and the results showed that 5a-dihydrotestosterone failed to increase intracellular cAMP in the presence of a-difluoromethylornithine, which suggests that polyamine synthesis is required for androgen increase of cAMP.…”
Section: Discussionmentioning
confidence: 93%